Principles and Applications in Nuclear Engineering Radiation Effects, Thermal Hydraulics, Radionuclide Migration in the Environment - Abdel Rahman, Rehab O.; El-Din Saleh, Hosam M. (IntechOpen, 2018)
Nuclear engineering could be viewed as the engineering field that ensures optimum and sustainable technological applications of natural and induced radioactive materials in different industrial sectors. This book presents some advanced applications in radiation effects, thermal hydraulics, and radionuclide migration in the environment. These scientific contributions from esteemed experts introduce some nuclear safety principals, current knowledge about radiation types, sources and applications, thermal properties of heat transfer media, and the role of sorption in retarding radionuclide migration in the environment. This book also covers the advances in identifying radiation effects in dense gas-metal systems, application of dense granular materials as high power targets in accelerator driven systems and irradiation facilities, evaluation of boiling heat transfer in narrow channels, and application of fluorescence quenching techniques to monitor uranium migration.